LAYANAN INFORMASI PADA RUMAH SAKIT MAMAMI KOTA KUPANG BERBASIS WEBS - Zampi, Aprilia Ch; Malahina, Edwin A. U.; Saitakela, Mardhalia (STIKOM Uyelindo Kupang, 2020)
Kupang City is municipality city and East Nusa Tenggara Capital city at once. Its glowing population, from time to time, causing varied problems, as such, in creasing pollution, limitedness resources, infrastructures and economic growth, thus generate broad impact, without exception, public healt threatening. Mamami Hospital is a prevate ownership healty mean in Kupang city,runing public trasition healt service, by general practioner, medical specialis on tooth , child, midwife service,internal disease, surgical operation, ophthaltmologist, tediarticiant, public care healt reference. Mamami Hospital, estimated, faces to potential problems, first, of its ignorance healt care information by a large member of Kupang‘s population, and second, possesses no available and accurate data on its patiens recording on digital device. Personally to thanks every one, the owner especeally, who received me to practice my digital device application skill at Mamami Hospital, writer would like to contributed a public information for mamami hospital. Further information on method of this research, researcher uses discription, bibliography observation and interview. Based on above finding, writer apprently suggest Mamami Hospital’s, agent to answer its need to cultivate in their relationsip with patients by public health information from digital device. This public information facilitate them to communicate each other on their need.